PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI BLANCO COFFEE YOGYAKARTA - Uswatun Chasanah; Gita Prihatiningtyas (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
The point of overall study was to determine the impact of marketing mix on consumer purchasing decisions at Blanco Coffee Yogyakarta. The sort of investigation employed was descriptive quantitative and employs the survey strategy. The people surveyed included Blanco Coffee Yogyakarta customers. Its sampling method entails non-probability procedures, i.e., incidental sampling, including a representative of 100 individuals. Data analysis methods use multiple linear regression with assistance of large - scale application software SPSS 23. The investigation 's findings revealed that sample t - test could be used to identify two consecutive independent variables which have a substantial impact on the purchase decision, particularly regarding product and physical evidence, whereas the variables which do not possess a substantial impact on this same purchase decision are process, people, promotion, place, and price. At the same time, overall marketing mix does have a considerable impact on purchasing decisions having valuation F (5,214) > F-table (2,11). According to the findings of the study, overall marketing mix does have a 23 percent impact upon purchasing decisions, whereas the additional 77 percent is regulated by several other elements.